Tremble before the Lord: myth and history in Psalm 114 - Prinsloo, G. T. M. (Old Testament Essays, 1998)
Psalm 114 summarises the history of Israel in poetic form. Language associated with theophanies is used to produce a unique hymn commemorating God's saving acts. Particularly interesting is the intertwining of motifs from history and myth to give a concise overview of God's gracious dealings with his people. This feature has often been recognised, but its interpretation has led to widely diverging views on the date and social setting of the psalm. Extratextual material is often used as key to interpret the poem. In the present study, the key to the interpretation of Psalm 114 is sought in the poem itself. First, a detailed intratextual analysis of the poem with special emphasis on the poetic intertwining of historical and mythological elements is given. Second, the poem's intertextual relationships are analysed. Here attention is also given to its place in the Book of Psalms and its interpretation in Jewish and Christian tradition. From these analyses some conclusions about the date and social setting(s) of the psalm are drawn.
free
Keywords: Christianity; Psalm 114